Transmit Beamspace-Based Unitary Parallel Factor Method for DOD and DOA Estimation in Bistatic MIMO Radar - Baoqing Xu (IEEE Access, 2018)
In this paper, a novel transmit beamspace (TB)-based unitary parallel factor (PARAFAC) algorithm is proposed for direction-of-departure (DOD) and direction-of-arrival estimation in bistatic multiple-input multiple-output (MIMO) radar. A modified TB matrix is designed through convex optimization to focus the transmitted energy in the desired spatial sector. Due to the influence of the TB matrix, the tensor model after forward-backward averaging for TB-based bistatic MIMO radar cannot be written as a PARAFAC tensor model. To solve this problem, we have serious requirement for the structure of the TB matrix, which is indispensable in constructing the real-valued PARAFAC model. Based on this precondition, the TB technique can be successfully combined with the unitary PARAFAC (U-PARAFAC) method. Moreover, a look-up table is built to compensate the DOD estimation bias, which actually establishes the mapping relationship for DOD. The Cramer-Rao bound on angle estimation in TB-based bistatic MIMO radar is also derived for performance comparison. Simulation results demonstrate the effectiveness of the proposed algorithm.